2017
DOI: 10.1088/1674-4527/17/2/11
|View full text |Cite
|
Sign up to set email alerts
|

Effects of non-Newtonian gravity on the properties of strange stars

Abstract: The properties of strange star matter are studied in the equivparticle model with inclusion of non-Newtonian gravity. It is found that the inclusion of non-Newtonian gravity makes the equation of state stiffer if Witten's conjecture is true. Correspondingly, the maximum mass of strange stars becomes as large as two times the solar mass, and the maximum radius also becomes bigger. The coupling to boson mass ratio has been constrained within the stability range of strange quark matter.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
10
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(10 citation statements)
references
References 49 publications
0
10
0
Order By: Relevance
“…Effects of non-Newtonian gravity on the properties of neutron stars and SSs have been studied extensively [e.g., [11][12][13][14][15][16][17][18][19]. The conventional inverse-square-law of gravity is expected to be violated in the efforts of trying to unify gravity with the other three fundamental forces, namely, the electromagnetic, weak and strong interactions [20][21][22].…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…Effects of non-Newtonian gravity on the properties of neutron stars and SSs have been studied extensively [e.g., [11][12][13][14][15][16][17][18][19]. The conventional inverse-square-law of gravity is expected to be violated in the efforts of trying to unify gravity with the other three fundamental forces, namely, the electromagnetic, weak and strong interactions [20][21][22].…”
Section: Introductionmentioning
confidence: 99%
“…The contribution of the Yukawa correction V Y (r) of Eq. ( 13) to the energy density of SQM is obtained by integrating over the quark densities n b ( x 1 ) and n b ( x 2 ) inside a given volume V [11,12,17,51],…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…[17] and references therein). Effects of non-Newtonian gravity on the properties of NSs and QSs have been studied [18][19][20][21][22], and it is found that the inclusion of non-Newtonian gravity will lead to the stiffening of the EOS and a bigger maximum mass of the stars.…”
mentioning
confidence: 99%
“…Non-Newtonian gravity will be introduced following Refs. [18][19][20]. According to Fujii [16], non-Newtonian gravity can be described by adding a Yukawa term to the conventional potential between two objects with masses m 1 and m 2 , i.e.,…”
mentioning
confidence: 99%